Determinants of employee turnover in manufacturing company - Ng, Chee Kean (2015)
The main objective of this research is to focus on determinants of employee turnover in manufacturing company. Employee turnover is always a major issue being discussed in the manufacturing company in Malaysia therefore the objective of this research is to find out the correlation of employee turnover and human resources practices which consist of training and development, compensation and benefit, career development, and supervisor support. The Pearson’s correlation and multiple regression tests were used to identify the relationship between employee turnover and training and development, compensation and benefit, career development and supervisory support. The result of the correlation analysis suggested that training and development, compensation and benefits, career development and supervisory support are correlated to the employee turnover. The multiple regression results indicated that there is a negative relationship between employee turnover and compensation and benefits. However, training and development, career development and supervisory support showed no significant relationship to the employee turnover. Based on the results, some recommendation are proposed and the limitations of the study being discussed. These shall provide opportunity to improve for future research